(untitled) (Journal of the College of Basic Education, 2024)
A type of cultural tourism known as educational tourism offers visitors and students the opportunity to learn new information about different civilizations worldwide. It also allows visitors to experience and learn by studying at colleges, universities, and schools, attending conferences and workshops, seeing historical and artistic exhibitions, and visiting historical sites. Furthermore, educational tourism is an economic resource that helps turn the wheel of economic development. Since there are no official or scholarly studies to assess the function of educational tourism in the Babylon Governorate, one will discover that some barriers result in the industry’s limited influence and poor role in the region’s growth. Thus, this study aims to assess educational tourism in the Babylon Governorate by investigating the notion of educational tourism, its advantages and varieties, and the accessibility of its constituent parts, ultimately leading to the researcher’s conclusions and suggestions.